The Sense of Touch and its Impact on Marketing: A Theory Development Analysis - Brondino Pompeo, Karin Ligia (2012)
The haptic interaction with products, people and components in shopping environment involves, besides the physical response, a physiological response. Both academia and marketers show increasing interest in the sense of touch and its particularities and impacts on consumer behavior. Although present since the 1980s, studies related to the sense of touch and its consequences and applications for marketing began to have higher volume and better understanding of their characteristics in the last ten years it is therefore a subject still in its infancy from the standpoint of theoretical construction. This article aims to analyze the development of the theory of touch in marketing, developing a brief description of the evolution of findings on the subject and presenting a critical analysis of the theoretical evolution, using the six criteria proposed by Sheth, Gardner and Garrett (1988): structure, specification, testability, empirical support, richness and simplicity. The theory of touch in marketing received a positive evaluation. This research may contribute: (1) to practitioners, as a summary of existing knowledge on the subject, and (2) to researchers interested in the subject, as a broad overview on the theory development, as well as a guide to the main available literature and a mapping on the findings and possible gaps for research.